Adaptive impedance control for unknown time-varying environment position and stiffness - Zainul Azlan , Norsinnira; Yamaura, Hiroshi (World Academy of Science, Engineering and Technology, 2013)

(untitled)
This study is concerned with a new adaptive impedance control strategy to compensate for unknown time-varying environment stiffness and position. The uncertainties are expressed by Function Approximation Technique (FAT), which allows the update laws to be derived easily using Lyapunov stability theory. Computer simulation results are presented to validate the effectiveness of the proposed strategy.